Introduction: Young Fatherhood: Lived experiences and policy challenges. Issue 1 (24th November 2015) - Neale, Bren
Abstract : The entry of young people into early parenthood has long been regarded as an issue for social policy and for professional practice in the UK and internationally. Despite a steadily falling trend, most notably since 1998, the UK still has one of the highest rates of teenage pregnancy in Europe, concentrated in the most socially disadvantaged areas of the country (Office for National Statistics, 2015 ). The majority of these pregnancies are unplanned, with about half resulting in the birth of a child, although the extent to which this should be a cause for concern is a contested issue (Duncan et al., 2010 ). Considerable research evidence exists on the experiences of young mothers, with a range of interventions designed to meet their needs. However, young fathers (defined as those under the age of 25, a quarter of whom are estimated to be in their teens) have, until recently, been neglected in both research and policy. Over the past decade, small pockets of research evidence on the circumstances, practices and values of young fathers have begun to coalesce into a fledgling evidence base. However, the notion of 'feckless' young men, who are assumed to be absent, or disinterested in 'being there', or, worse, regarded as a potential risk to their children, continues to hold sway, particularly in popular media and some political discourses (Neale and Davies, 2015 ).